Chemical modification of peptides by hydrazine. - Honegger, A (1981)
High pressure ('performance') liquid chromatography on reverse-phase supports has been used to characterize the products arising from the hydrazine treatment of peptides. In addition to converting arginine residues into ornithine, the reaction was found to cleave predominately Gly-Xaa, Xaa-Gly, Asn-Xaa and Xaa-Ser peptide bonds. Peptide-bond cleavage and deguanidation was studied as a function of time of exposure to hydrazine, hydrazine concentration and temperature. The convenience of this method of chromatography for the rapid low-cost separation and isolation of peptides, as well as their reaction products, is illustrated at the level of material required for solid-phase microsequencing.